Ovary Size in Wheat (Triticum aestivum L.) is Related to Cell Number. Issue 2 (2nd February 2017) - Reale, L.; Rosati, A.; Tedeschini, E.; Ferri, V.; Cerri, M.; Ghitarrini, S.; Timorato, V.; Ayano, B. E.; Porfiri, O.; Frenguelli, G.; Ferranti, F.; Benincasa, P.
Abstract : In wheat and other grain species, variations in kernel size are related to variations in ovary size. It is not known whether environmental factors that are known to affect kernel size may also affect ovary size, thus maintaining the kernel size‐ovary size correlation. Additionally, it is not known whether variations in ovary size in wheat depend on cell size, cell number or both. In this study, ovary size was measured with a stereomicroscope, and ovary wall cell size and number were measured in equatorial cross‐sectional areas of the ovary wall in two common wheat cultivars with different kernel size: Bora (large kernels) and Bologna (small kernels). Plants were grown at low and high N fertilization (0 and 240 kg ha −1 ) with normal density (450 seeds m −2 ), and at low and high plant density (200 and 650 plants m −2 ) with normal fertilization (160 kg N ha −1 ). The variation in ovary wall size across all data pooled (i.e., including two genotypes, two N and two density treatments, and including within treatment variations), was related to cell number and not to the cell size, which did not vary significantly with cultivar and field practices. With increasing ovule size, ovary wall size increased less than proportionally, thus the ovule/ovary ratio increased. Cell size in the ovary wall showed an upper limit across all treatments, which decreased with increasing cell number. These findings may be useful for breeding programs and field practices aimed at increasing kernel size and yield.